Design and implementation of a recirculating aquaculture system for research purposes in Marine science center, university of Basrah- IRAQ - Ahmed, Arafat R.; Ali, Malik H.; Almukhtar, Mustafa A. (Iraqi Journal of Aquaculture, 2016)
The design and implementation a recirculating aquaculture system was discussed, which is considered to be the first of its kind at Iraqi universities and research centers that specialize in aquaculture. The system was designed based on standard specifications and built from materials available in local markets. The system consists of 16 fiberglass tanks (each measuring approximately 75×75×45 cm with a capacity of roughly 250 L). We showed that the new system maintained appropriate environmental conditions for aquatic organisms during the trial period. Moreover, this type of rearing system aids in water conservation and keep on controlled experiment condition.